Encoding method of dinamik image stationary background in infocommunication system - Бараннік, Володимир Вікторович; Леках, Альберт Анатолійович; Остроумов, Борис Володимирович (Ukrainian Information Security Research Journal, 2013)
In order to improve the performance of communication systems is necessary to improve the compression technology of dynamic images. Therefore justified the basic principles of a compression method of dynamic images of stationary background in information and communication systems on the basis of the formation of differential represented by the frame. In order to identify the dynamic component of the threshold set out the terms of use filtration differential represented the frame. The technology of splitting differentially represented on the frame components: the dynamic component, a binary mask stationary background and an array of characters. The technology of processing dynamic component, conducted on the basis of a one-dimensional position-encoding with adaptive selection of the base. The basic steps of the method of processing the binary mask differentially represented by the frame, carried out on the basis of coding capacity of the two lengths of the binary alphabet series. Constructed a matrix decoding technology signs, implemented on the basis of coding capacity alphabet with the structural similarity with the matrix of the binary mask. It is shown that the developed coding methods provide the potential for further reduction in volume and increasing die compression of dynamic images stationary background, which generally leads to a reduction of processing time in information and communication systems.